Oocyte donation for stem cell research - Mertes, H.; Pennings, G. (Human reproduction (Oxford), 2007)
The future success of stem cell research by means of somatic cell nuclear transfer (SCNT) depends on a sufficient supply of human oocytes. However, oocyte donation presents certain risks for the donor, and concerns for women’s welfare are rightly vocalized. At the same time, these risks are comparable with the risks faced by other healthy research subjects. Thus, research donation can withstand ethical scrutiny if it fulfils the same conditions as other research involving healthy human subjects. Specifically, this means that the benefits of the research project need to outweigh the harms, that risks must be minimized, that informed consent has to be guaranteed by averting undue inducement and the recruitment of vulnerable women and that donors can and should be reimbursed for their research participation.